2020
DOI: 10.1016/j.atherosclerosis.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in COVID-19: Current findings and therapeutic implications

Abstract: Coronavirus disease 2019 (COVID-19) increases the risk of several non-pulmonary complications such as acute myocardial injury, renal failure or thromboembolic events. A possible unifying explanation for these phenomena may be the presence of profound endothelial dysfunction and injury. This review provides an overview on the association of endothelial dysfunction with COVID-19 and its therapeutic implications. Endothelial dysfunction is a common feature of the key comorbidities that increase risk for severe CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
255
1
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(280 citation statements)
references
References 58 publications
5
255
1
19
Order By: Relevance
“…However, high BP variability was related with high risks of mortality and ICU admissions, underlying the importance of maintenance of stable in-hospital BP in these patients. Increased BP variability could reflect increased arterial stiffness and endothelial dysfunction that are associated with cardiovascular events ( 24 , 25 ). Additional explanation could be a sudden BP decline because of progressive deterioration of underlying conditions.…”
Section: The Influence Of Blood Pressure Control In Covid-19mentioning
confidence: 99%
“…However, high BP variability was related with high risks of mortality and ICU admissions, underlying the importance of maintenance of stable in-hospital BP in these patients. Increased BP variability could reflect increased arterial stiffness and endothelial dysfunction that are associated with cardiovascular events ( 24 , 25 ). Additional explanation could be a sudden BP decline because of progressive deterioration of underlying conditions.…”
Section: The Influence Of Blood Pressure Control In Covid-19mentioning
confidence: 99%
“…On the other hand, great care should be taken to avoid any adverse interactions between lipid-lowering medications and drugs that might be used to treat COVID-19 (for instance, some antiviral agents) [59] , especially in patients with abnormal liver function tests or myopathies [77] . One caveat is that, while there is no reason to stop statin therapy in patients hospitalized for COVID-19, the level of evidence remains too low—in the absence of RCTs, some of which are ongoing as reported elsewhere [38] , [78] , [79] , although the impact of their results may be attenuated by successful vaccine strategies in the future—to justify initiating statin therapy in statin-free patients in hopes of reducing the burden of disease and improving clinical outcomes [38] , [80] .…”
Section: Discussionmentioning
confidence: 99%
“…As the endothelial system primarily functions to prevent the passage of harmful substances into our circulatory system, this renders multiple organ systems vulnerable to COVID-19 infiltration and infection ( 61 ). Despite ACE2 serving as the entry point for this virus, ACE2 also has protected against pulmonary infections, indicating that increasing ACE2 is a possible treatment option for COVID-19 infections ( 75 ).…”
Section: Covid-19 Effects On the Cardiovascular System And Correspondmentioning
confidence: 99%
“…Further studies have shown significant promise in utilizing rein-angiotensin inhibitors and statins to improve endothelial function and offer protective effects. These drug classes have known benefits on the endothelium, such as quelling inflammation, reversing endothelial tissue damage, and preventing thrombus formation ( 75 ). It is not surprising that statins are currently being evaluated for their efficacy in reducing COVID-19 symptoms associated with endothelial dysfunction, as prior studies have suggested these drugs may be promising treatment options for other viral infections, including viral pneumonia and the influenza virus ( 73 ).…”
Section: Covid-19 Effects On the Cardiovascular System And Correspondmentioning
confidence: 99%
See 1 more Smart Citation